Electronic Records Management (ERM) practices at the Malaysian Federal Ministries: exploring the fundamental organizational and professional issues / Irwan Kamaruddin Abd. Kadir - Abd. Kadir, Irwan Kamaruddin (2014)
This study is an attempt to gain greater understanding of the importance of departmental records officers' (in Malaysian Government they are called Tegawai Rekod Jabatan' (PRJ)) roles and responsibilities on electronic records (e-records). The study adopted a case study approach that combined both quantitative and qualitative data. Quantitative data were gathered in the first phase of the study from 45 agencies under the Prime Minister's Department. In the second phase of the study, qualitative data were gathered from face-to-face interviews with three PRJs from three agencies under the Prime Minister's Department. To verify data gathered in the second phase of the study, four focus group (FG) discussions with 120 PRJs from 24 ministries and related agencies were conducted in the third phase of the study. The data derived from the PRJ have fulfilled the objectives of the study which are: To identify the record managers' perspectives with regard to their responsibilities in managing e-records within the context of fundamental organizational requirements; To find out the record managers' perspectives with regard to their responsibilities in managing e-record within the context of professional requirements; and To ascertain factors that contribute to the surveyed records managers' perspective about the fundamental organizational and professional issues that limit the implementation of their responsibilities on e-records as required by the "Elektronik-Strategi Pemeliharaan Arkib dan Rekod Kerajaan" (e-SPARK) project deliverables. Overall the data suggested that the PRJs' perspectives on their roles and responsibilities which relates to the fundamental organizational and professional issues were influenced by the larger policy, organizational and professional context in which they function. Powerful forces from the top affected ERM practices by giving limited focus on PRJs' roles and responsibilities and providing limited resources to PRJs for their career development on ERM as required by the e-SPARK project. Therefore, understanding on how PRJs work on e-records require an understanding how contextual factors shape and constrain PRJs' practices based on the fundamental organizational and professional issues surrounding their roles and responsibilities on ERM in the Malaysian Federal Government agencies.